Treatment of rabbit cheyletiellosis with selamectin or ivermectin: a retrospective case study - Bergvall Kerstin; Mellgren Marianne (Acta Veterinaria Scandinavica, 2008)
Abstract Background A retrospective study of rabbits treated against cheyletiellosis was performed to evaluate the efficacy and safety of selamectin or ivermectin in clinical practice. Methods Medical records from 53 rabbits with microscopically confirmed Cheyletiella infestation were collected from two small animal clinics. The rabbits were divided into three groups, based on treatment protocols. Group 1 included 11 rabbits treated with ivermectin injections at 200–476 μg kg-1 subcutaneously 2–3 times, with a mean interval of 11 days. In Group 2, 27 rabbits were treated with a combination of subcutaneous ivermectin injections (range 618–2185 μgkg-1) and oral ivermectin (range 616–2732 μgkg-1) administered by the owners, 3–6 times at 10 days interval. The last group (Group 3) included 15 rabbits treated with selamectin spot-on applications of 6.2–20,0 mgkg-1, 1–3 times with an interval of 2–4 weeks. Follow-up time was 4 months–4.5 years. Results Rabbits in remission were 9/11 (81,8%), 14/27 (51,9%) and 12/15 (80,8%) in groups 1, 2 and 3, respectively. Conclusion All treatment protocols seemed to be sufficiently effective and safe for practice use. Though very high doses were used in Group 2 (ivermectin injections followed by oral administration), the protocol seemed less efficacious compared to ivermectin injections (Group 1) and selamectin spot on (Group 3), respectively, although not statistically significant. Controlled prospective studies including larger groups are needed to further evaluate efficacy of the treatment protocols.